Library Strategies in Supporting National Literacy Development in Indonesia - Pirmanto, Dovel; Efrinandes, Haza; Kumala Sari, Rani; Prayera, Aulia Dwinda (Al-Ijtima`i: International Journal of Government and Social Science, 2025)
Library management is an important aspect in increasing literacy interest among students. Mistakes in choosing strategies and management can have a negative impact on student visits and literacy. This study aims to analyze the role of library management in increasing students literacy interest at Kerinci 1 State Junior High School. The research method used in this study is qualitative descriptive research, data was collected through observation, interviews, and documentation from various related parties, including librarians, teachers, and students. The results of the study show that good library management strategies, such as managing a diverse collection of books, providing comfortable facilities, and literacy programs such as reading clubs and reading competitions, have a significant impact on increasing students interest literacy. In addition, support from the school in terms of budget, librarian training, and technological innovation, such as a digital library system, also strengthen the library appeal to students. In conclusion, effective and structured library management is able to create a conducive learning environment and support students interests literacy at Kerinci 1 State Junior High School.